Extensive Reading: A Reading Intervention for Chinese EFL Students with Different Reading Self-Efficacy Levels - Dai, Manman; Chinwonno, Apasar (An Online Journal of Education, 2023)
English language teaching in rural Chinese high schools has not only been methodologically backward, but also impractical in content and approach, it led to distract student motivation, decrease language abilities, and even diminish reading improvement. The purpose of this study was to 1) investigate the effects of extensive reading on the English reading comprehension of Chinese EFL students with low reading self-efficacy; 2) investigate the effects of extensive reading on the English reading comprehension of Chinese EFL students with high reading self-efficacy, and 3) explore Chinese EFL students’ reading self-efficacy after participating in an English extensive reading intervention. Fifty-four Chinese high school students selected by purposive sampling participated in a twelve-week mixed-methods study. The research instruments included (1) an English reading comprehension test; (2) a reading self-efficacy questionnaire; (3) a semi-structured interview, and (4) a reading log. Quantitative data from a paired samples t-test indicated that students with both low and high reading self-efficacy had significant improvements in English reading comprehension at a level of 0.05. The qualitative data also showed that the sense of achievement experienced by the students was also different for each reading self-efficacy group. Recommendations also offered how students with different reading self-efficacy levels efficaciously interacted with the extensive reading intervention.